Injury prevention among young people in nursing homes: Recommendations following expert consultation forums. (22nd November 2020) - Cartwright, Anna; Bugeja, Lyndal; Ibrahim, Joseph E.
Abstract: Background: Approximately 6, 000 people under the age of 65 years reside in nursing homes each year in Australia. These young people in nursing homes are at risk of premature death and preventable morbidity from injuries. Choking and falls are the leading causes of premature deaths in this cohort with reported rates of 44% and 33%, respectively. Objectives: To develop injury prevention recommendations for young people in Australian nursing homes. Methods: This mixed‐methods study comprised two expert consultation panels and a follow‐up survey. Two expert and stakeholder consultation panels used a modified nominal group technique to formulate recommendations. A short survey was subsequently given to participants to validate responses from the panels and to provide an opportunity to evaluate and rank recommendations. Results: Ten recommendations were formulated for consideration that focused on system‐wide reforms. Four were ranked as most important for implementation: education and training for nursing home staff; implementation of National Disability Insurance Scheme; support for coordinated care; and increasing residential housing stock that is appropriately designed. Conclusion: Extensive changes are needed to prevent injury for young people in nursing homes. Implementation should reduce the risk of injury and lead to an improved quality of life for this cohort. Implications for practice: This study provides an evidence base for aged care practitioners to improve practice within nursing homes to reduce fatal and non‐fatal injuries for young people in nursing homes.